Aluminum-copper-cerium heat-resistant aluminum alloy and preparation method thereof

By reasonably proportioning Cu, Ce, Mn, Sc and Zr elements in aluminum-copper-cerium-based heat-resistant aluminum alloys and optimizing the heat treatment process to form a nanoprecipitated phase and a micrometallic compound network, the problem of insufficient mechanical strength of the existing cast heat-resistant aluminum alloys at high temperatures is solved, and the high-temperature mechanical properties of the alloy are significantly improved.

CN119640109APending Publication Date: 2025-03-18SHANGHAI JIAOTONG UNIV

Patent Information

Application Number
CN202411655916.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The mechanical strength and sustainability of existing cast heat-resistant aluminum alloys at 300°C to 400°C are difficult to meet the latest demands in the automotive and aerospace fields.

Method used

Aluminum-copper-cerium-based heat-resistant aluminum alloy is used to form a nanoprecipitated phase and a micrometallic compound network by reasonably proportioning Cu, Ce, Mn, Sc and Zr elements, and optimize the heat treatment process to improve the high-temperature mechanical properties of the alloy.

Benefits of technology

It significantly improves the long-term service capability of cast heat-resistant aluminum alloys at high temperatures, improves the yield strength and tensile strength at 300℃ and 400℃, and is better than traditional ZL206 and ZL207 alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640109A_ABST
    Figure CN119640109A_ABST
Patent Text Reader

Abstract

The invention provides an aluminum-copper-cerium heat-resistant aluminum alloy and a preparation method thereof. The aluminum-copper-cerium heat-resistant aluminum alloy comprises the following components in percentage by weight: 7%-9.5% of Cu, 1.3%-2.3% of Ce, 0.1%-0.5% of Mn, 0.1%-0.4% of Sc, 0.1%-0.4% of Zr and the balance of Al and inevitable impurities. The structure morphology of the heat-resistant aluminum alloy is an isometric crystal, coarse precipitation Al3 (Sc, Zr) exists in the isometric crystal, and the heat-resistant aluminum alloy is an alpha-Al nucleating agent; a large number of high-thermal-stability L12Al3 (Sc, Zr) with the size smaller than or equal to 10 nm and a large number of Al2Cu nanoscale dispersed precipitated phases with the thickness smaller than or equal to 10 nm are separated out in crystal grains, and granular and lamellar Al24MnCu8Ce3, Al16Cu4Mn2Ce and Al8CeCu4 micron-scale heat-resistant intermetallic compound networks are continuously distributed along the crystal boundary. The heat-resistant aluminum alloy is excellent in high-temperature performance and high in high-temperature yield strength and tensile strength and is superior to a traditional ZL206 alloy (T6) and a traditional ZL207 alloy (T6), and the long-term service capacity of the cast heat-resistant aluminum alloy at the high temperature is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technology of heat-resistant aluminum alloy materials, and in particular relates to an aluminum-copper-cerium series heat-resistant aluminum alloy and a preparation method thereof. Background Art

[0002] In the automotive market, aluminum and its alloys are mainly used to manufacture powertrain components, including engines, clutches, transmissions, and various drive shafts due to their high specific strength. The amount of aluminum and its alloys accounts for 70% of the total amount of automobiles, of which cast aluminum alloys constitute the main part (~85-90%), mainly based on the Al-Si eutectic system. Improving the mechanical strength and sustainability of aluminum alloys at high temperatures is a major technical goal, because most engine parts, such as cylinder heads, valve filters, are exposed to temperatures exceeding 200°C and can be replaced with newer high-strength alloys. This in turn can lead to higher engine operating temperatures and thus improve efficiency. It is well known that the addition of Cu and Mg to Al-Si alloys can strengthen the alloy by precipitating coherent intermetallic phases. However, when the temperature is above 200°C, the precipitates quickly coarsen, resulting in a loss of alloy strength.

[0003] Cheng Jianing and others improved the heat resistance of aluminum alloy by microalloying, thus developing ZL206 alloy, wherein the chemical composition of ZL206 is Cu: 7.6-8.4wt.%, RE: 1.5-2.3wt.%, Mn: 0.7-1.1wt.%, Zr: 0.1-0.25wt.%, Al is the balance, wherein RE is mixed rare earth. In the T6 state, the high temperature tensile tensile strength of ZL206 alloy at 300℃ is 161MPa, the high temperature tensile tensile strength of ZL207 alloy at 300℃ is 115MPa, the high temperature tensile tensile strength at 400℃ is 70MPa, and the elongation is less than 2%, but the high temperature strength performance indicators of these aluminum alloy materials are still difficult to meet the latest needs of the current automotive and aerospace fields. Summary of the invention

[0004] In view of the prominent problem that the strength of existing cast heat-resistant aluminum alloys cannot meet industrial needs at 300℃-400℃ (tensile strength at 300℃ is less than 180MPa, and tensile strength at 400℃ is less than 70MPa), the present invention provides an aluminum-copper-cerium series heat-resistant aluminum alloy and a preparation method thereof. The heat-resistant aluminum alloy has excellent high-temperature performance, high high-temperature yield strength and tensile strength, is superior to traditional ZL206 alloy (T6) and ZL207 alloy (T6), and significantly improves the long-term service capability of the cast heat-resistant aluminum alloy at high temperatures.

[0005] To achieve the above object, the technical solution of the present invention is:

[0006] An aluminum-copper-cerium series heat-resistant aluminum alloy, characterized in that it comprises, by weight percentage: Cu: 7% to 9.5%, Ce: 1.3% to 2.3%, Mn: 0.1% to 0.5%, Sc: 0.1% to 0.4%, Zr: 0.1% to 0.4%, and the balance is Al and unavoidable impurities;

[0007] Wherein, the mass relationship between Cu and Ce is Cu=2Ce+4-5; the total molar fraction of the Ce-containing heat-resistant intermetallic compound is ≥2%;

[0008] The aluminum-copper-cerium series heat-resistant aluminum alloy has a yield strength of 190-200 MPa, a tensile strength of 205-215 MPa and an elongation of 5-8% at 300°C; a yield strength of 100-108 MPa, a tensile strength of 112-120 MPa and an elongation of 10-15% at 400°C.

[0009] According to the Al-Ce-Cu ternary alloy phase diagram, Al 8 C 4 and Al 2 Cu phase, in order to make the alloy produce aging strengthening effect, the concentration of Cu / Ce>2 is required. At the same time, in order to avoid excessive Cu from being insoluble during solution treatment, the content relationship of Cu and Ce is required to be Cu=2Ce+4~5. Adding a small amount of Mn (0.1%~0.5%) further accelerates and strengthens the aging hardening effect during aging, and improves the stability of the precipitated phase through solute interface segregation during thermal exposure. The composite addition of Sc and Zr promotes the formation of equiaxed crystals, refines the grain size, and precipitates thermally stable L1 during pre-aging. 2 Al 3 (Sc, Zr) nano-precipitation phase. Finally, the composition of the aluminum-copper-cerium series high-temperature high-strength casting heat-resistant aluminum alloy was designed, so that Al2O3 precipitates along the grain boundaries during the solidification process. 24 MnCu 8 Ce 3 、Al 16 Cu 4 Mn 2 Ce and Al 8 C 4 Intermetallic compound phase, intracrystalline precipitation L1 2 Al 3 (Sc, Zr) and Al 2 Cu phase; Al is precipitated first 3 (Sc, Zr) acts as nucleating agents, promoting the formation of equiaxed crystals and refining the grain size.

[0010] Furthermore, in order to ensure that the intermetallic compounds at the grain boundaries can form a semi-continuous or continuous network, the total molar fraction of the Ce-containing heat-resistant intermetallic compounds is required to be ≥2%.

[0011] The microstructure of the heat-resistant aluminum alloy is equiaxed crystals, and coarse Al 3 (Sc, Zr), which is an α-Al nucleating agent; a large number of high thermal stability L1 with a size of ≤10nm precipitates inside the grains 2 Al 3 (Sc, Zr) and Al with thickness ≤ 10nm 2 Cu nanoscale dispersed precipitate phase, granular and lamellar Al are continuously distributed along the grain boundaries. 24 MnCu 8 Ce 3 、Al 16 Cu 4 Mn 2 Ce and Al 8 C 4 Micrometer-scale heat-resistant intermetallic compound network.

[0012] Preferably, the alloy comprises, by weight percentage, 8.7% Cu, 1.9% Ce, 0.45% Mn, 0.32% Sc, 0.27% Zr, and the remainder is Al and inevitable impurities.

[0013] Based on the same inventive concept, the present invention also provides a method for preparing an aluminum-copper-cerium series heat-resistant aluminum alloy, comprising the following steps:

[0014] S1: Calculating the raw material ratio according to weight percentage, smelting the raw materials to obtain an aluminum alloy ingot and quenching the ingot;

[0015] S2: subjecting the aluminum alloy ingot obtained in step S1 to a solid solution treatment, specifically, maintaining the temperature at 200°C to 300°C for 12h to 24h, then heating the temperature to 350°C to 450°C for 5h to 15h, then heating the temperature to 520°C to 537°C for 5h to 15h, and finally quenching;

[0016] S3: subjecting the aluminum alloy ingot after the solid solution treatment to low temperature aging, specifically, quenching after keeping the temperature at 160°C to 200°C for 3h to 18h.

[0017] Preferably, the step S1 is specifically as follows: placing high-purity Al in an iron crucible and heating it to 720°C for melting, and then keeping it warm for 30 minutes; sequentially adding preheated pure Cu, Al-30wt.%Ce, and Al-10wt.%Mn master alloy ingots into the melt, stirring and melting them, and keeping them warm for 10 to 20 minutes each time; heating the melt to 760°C, sequentially adding preheated Al-2wt.%Sc and Al-10wt.%Zr master alloy ingots into the melt, stirring until all melted, and keeping them warm for 10 minutes; sequentially adding refining agent and hexachloroethane for degassing and deslagging, standing and keeping warm for 10 to 15 minutes after slagging, and finally casting into a mold preheated at 200°C to 300°C to obtain an aluminum alloy ingot; and quenching the aluminum alloy ingot once solidified.

[0018] Preferably, the temperature of the alloy melt during pouring in step S1 is 740°C to 760°C.

[0019] Preferably, the quenching is a water quenching treatment.

[0020] Due to the adoption of the above technical solution, the present invention has the following advantages and positive effects compared with the prior art:

[0021] (1) The aluminum-copper-cerium heat-resistant aluminum alloy provided by the present invention confirms that the concentration of Cu / Ce>2 is required through the solidification phase diagram. At the same time, in order to avoid excessive Cu from being unable to dissolve during solution treatment, the ratio of copper and cerium elements is Cu=2Ce+4~5, so as to adjust the volume fraction ratio of nano-precipitated phase and micro-metallic compound. The nano-precipitated phase is θ′-Al 2 Cu, micron intermetallic compound is Al 16 Cu 4 Mn 2 Ce、Al 8 Cu 4 Ce and Al 24 MnCu 8 Ce 3 Mutually. θ′-Al 2 The mechanism by which Cu nano-precipitates improve high-temperature strength is precipitation strengthening, and the mechanism by which micro-intermetallic compounds improve high-temperature strength is load transfer and inhibition of grain boundary sliding. Through phase diagram calculation, it is confirmed that the volume fractions of nano-precipitates and micro-intermetallic compounds can be increased simultaneously, so that the two strengthening mechanisms of precipitation strengthening and load transfer can produce the best synergistic effect at the same time, improving the high-temperature mechanical properties of the alloy.

[0022] (2) In order to solve the problem of θ′-Al 2 The strength decreases due to the dissolution of Cu nanoprecipitates. The addition of L1 2 Nano-precipitate forming elements, through L1 2The nano-precipitated phase significantly improves the long-term service capability of the heat-resistant cast aluminum alloy at high temperatures. In the preparation process of the aluminum-copper-cerium series heat-resistant aluminum alloy, a short heat treatment process is used to save production cycle and energy consumption for industrial applications as much as possible, including but not limited to pre-aging treatment at 200℃~300℃ / 12h~24h to form high-density solute atomic clusters, and pre-aging treatment at 350℃~450℃ / 5h~15h to form high-density thermally stable insoluble L1 with high-density solute atomic clusters as heterogeneous nucleation particles. 2 Al 3 (Sc, Zr) nanoprecipitation phase, using 520℃~537℃ solid solution segregation Cu, and ensuring high density L1 2 Al 3 The (Sc, Zr) nanoprecipitate phase is not significantly coarsened, and the low-temperature aging process of 160-200℃ / 3-18h is adopted. 2 Al 3 The (Sc, Zr) nanoprecipitate phase is a heterogeneous nucleation point precipitated θ′-Al 2 Cu precipitates and promotes the formation of Mn, Sc and Zr in the θ′-Al 2 The coherent and semi-coherent interfaces of Cu precipitates segregate, preventing solute exchange and significantly inhibiting the θ′-Al 2 The Cu precipitate phase coarsens and significantly increases the θ′-Al 2 The thermal stability of the Cu precipitate phase at 300°C to 400°C solves the outstanding problem of limited high temperature life of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a microstructure diagram of the aluminum-copper-cerium series heat-resistant aluminum alloy material of Example 1 of the present invention;

[0024] Figure 2 This is a transmission electron micrograph of the aluminum-copper-cerium series heat-resistant aluminum alloy material of Example 1 of the present invention, which shows the nanoscale θ′ / θ"-Al 2 Cu and L1 2 Al 3 (Sc, Zr) precipitation phase;

[0025] Figure 3 L1 in the aluminum-copper-cerium series heat-resistant aluminum alloy material of Example 1 of the present invention 2 -Al 3 (Sc, Zr), θ' / θ"-Al 2 Transmission electron dark field phase and EDS analysis of Cu precipitation phase;

[0026] Figure 4 The θ' / θ"-Al in the aluminum-copper-cerium series heat-resistant aluminum alloy material of Example 1 of the present invention 2 Transmission electron dark field phase and EDS analysis of Cu precipitation phase;

[0027] Figure 5 The AlCu of Comparative Example 1 of the present invention 8.2 Ce 1.8 Microstructure diagram of the alloy;

[0028] Figure 6 The AlCu of Example 1 of the present invention 8.7 Ce 1.9 Mn 0.53 Sc 0.36 Zr 0.27 Alloy and AlCu of Comparative Example 1 8.2 Ce 1.8 High temperature tensile curves of the alloy at (a) 300℃ and (b) 400℃. DETAILED DESCRIPTION

[0029] The design principle of the present invention is as follows:

[0030] The alloy composition is determined by the alloy's equilibrium solidification phase diagram. On the one hand, the intermetallic compound must have sufficiently high thermal stability (thermal stability temperature limit ~ 400 ° C), and in order to ensure a sufficient number of intermetallic compound phases to inhibit grain boundary sliding and provide sufficient load transfer strengthening, the total molar fraction of the heat-resistant phase must meet ≥ 2%; on the other hand, nano-aging precipitates must be precipitated in the crystal to make the alloy meet the basic room temperature strength requirements, and multi-step heat treatment can be performed to control its microstructure. Secondly, the intermetallic compounds formed during the solidification process cannot remove the L1 used to further strengthen the alloy. 2 Nano-precipitate phase forming elements. At the same time, multi-step aging treatment is carried out to first make the high thermal stability L1 2 The nano-precipitates are uniformly precipitated in large quantities under the pre-aging treatment, and then the traditional high-temperature solid solution-low-temperature aging (T6) treatment is carried out, so that the low thermal stability nano-precipitates in the crystal for room temperature strengthening are precipitated in large quantities, and the excessive coarsening of the low thermal stability nano-precipitates can be avoided, thereby obtaining the maximum nano-precipitation strengthening effect.

[0031] The following is a further detailed description of an aluminum-copper-cerium series heat-resistant aluminum alloy and a preparation method thereof proposed by the present invention in conjunction with the accompanying drawings and specific embodiments. The advantages and features of the present invention will become more apparent from the following description.

[0032] Example 1

[0033] 1. Aluminum-copper-cerium heat-resistant aluminum alloy, comprising, by weight percentage, Cu: 8.7%, Ce: 1.9%, Mn: 0.45%, Sc: 0.32%, Zr: 0.27%, and the balance being Al and unavoidable impurities.

[0034] 2. A method for preparing an aluminum-copper-cerium heat-resistant aluminum alloy, comprising:

[0035] S1: a. After mechanically grinding the surface of the metal raw material to remove the surface oxide scale, prepare the materials according to the designed composition ratio; the ingredients are proportioned according to the weight of about 2.5kg per ingot;

[0036] b. Place a high-purity Al ingot in an iron crucible and heat it to 720°C to melt, then keep it warm for 30 minutes; sequentially add the preheated pure Cu, Al-30wt.%Ce, and Al-10wt.%Mn master alloy ingots to the melt, stir and melt, and keep warm for 10 to 20 minutes each time; heat the melt to 760°C, sequentially add the preheated Al-2wt.%Sc and Al-10wt.%Zr master alloy ingots to the melt, stir until all are melted, and keep warm for 10 minutes;

[0037] c. Add refining agent and hexachloroethane in turn to degas and deslag, let it stand and keep warm for 10 to 15 minutes after deslagging, and finally cast it into a mold preheated at 200°C to 300°C to obtain an aluminum alloy ingot; quench the aluminum alloy ingot once it solidifies;

[0038] S2: Solution treatment: keep the alloy ingot at 200℃~300℃ for 12h~24h, then heat it to 350℃~450℃ and keep it for 5h~15h, then heat it to 520℃~537℃ and keep it for 5h~15h, and finally quench it in room temperature water;

[0039] S3: Low temperature aging: The alloy ingot is then kept in an oil bath furnace at 190°C for 12 hours and quenched into room temperature water.

[0040] 3. Organization and performance testing

[0041] The microstructure of the prepared material is Figure 1-3 As shown in the figure, the heat-resistant aluminum alloy microstructure strengthened by various intermetallic compounds is obtained, that is, the macroscopic microstructure of the material is equiaxed crystal (grain size ~ 50μm), and Al is precipitated first. 3 The (Sc, Zr) intermetallic compounds exist as nucleating agents in the α-Al matrix, and a high number density of nanoscale θ′ / θ"-Al 2 Cu and L1 2 Al 3 (Sc, Zr) precipitation phase, Ce and Mn elements are concentrated in θ′ / θ"-Al 2 On the Cu precipitate phase, micrometer-scale Al is distributed nearly continuously on the grain boundary. 16 Cu 4 Mn 2 Ce、Al 24 Cu 8 Ce 3 Mn and Al 8 C 4 Intermetallic network.

[0042] Figure 4 The tensile stress-strain curves of the heat-resistant aluminum alloy material at 300℃ and 400℃ after heat treatment. The mechanical properties test results show that the yield strength and tensile strength of the prepared material at room temperature are 280MPa and 357MPa respectively, the yield strength and tensile strength at 300℃ are 200MPa and 210MPa respectively, the yield strength and tensile strength at 400℃ are 106MPa and 114MPa respectively, the tensile strength at 300℃ is 31% better than that of ZL206 alloy, 90% better than that of ZL207 alloy, and the tensile strength at 400℃ is 64% better than that of ZL207 alloy.

[0043] Example 2

[0044] 1. Aluminum-copper-cerium heat-resistant aluminum alloy, comprising, by weight percentage, Cu: 7.5%, Ce: 1.4%, Mn: 0.32%, Sc: 0.27%, Zr: 0.33%, and the balance being Al and unavoidable impurities.

[0045] 2. A method for preparing an aluminum-copper-cerium heat-resistant aluminum alloy, comprising:

[0046] S1: a. After mechanically grinding the surface of the metal raw material to remove the surface oxide scale, prepare the materials according to the designed composition ratio; the ingredients are proportioned according to the weight of about 2.5kg per ingot;

[0047] b. Place a high-purity Al ingot in an iron crucible and heat it to 720°C to melt, then keep it warm for 30 minutes; sequentially add the preheated pure Cu, Al-30wt.%Ce, and Al-10wt.%Mn master alloy ingots to the melt, stir and melt, and keep warm for 10 to 20 minutes each time; heat the melt to 760°C, sequentially add the preheated Al-2wt.%Sc and Al-10wt.%Zr master alloy ingots to the melt, stir until all are melted, and keep warm for 10 minutes;

[0048] c. Add refining agent and hexachloroethane in turn to degas and deslag, let it stand and keep warm for 10 to 15 minutes after deslagging, and finally cast it into a mold preheated at 200°C to 300°C to obtain an aluminum alloy ingot; quench the aluminum alloy ingot once it solidifies;

[0049] S2: Solution treatment: keep the alloy ingot at 200℃~300℃ for 12h~24h, then heat it to 350℃~450℃ and keep it for 5h~15h, then heat it to 520℃~537℃ and keep it for 5h~15h, and finally quench it in room temperature water;

[0050] S3: Low temperature aging: The alloy ingot is then kept in an oil bath furnace at 190°C for 10 h and quenched into room temperature water.

[0051] 3. Performance testing

[0052] The results of mechanical properties tests show that the yield strength and tensile strength of the prepared material at room temperature reach 2680MPa and 335MPa respectively, the yield strength and tensile strength at 300℃ reach 191MPa and 205MPa respectively, and the yield strength and tensile strength at 400℃ reach 101MPa and 112MP respectively.

[0053] Example 3

[0054] 1. Aluminum-copper-cerium heat-resistant aluminum alloy, comprising, by weight percentage, Cu: 8.2%, Ce: 1.6%, Mn: 0.38%, Sc: 0.22%, Zr: 0.35%, and the balance being Al and unavoidable impurities.

[0055] 2. A method for preparing an aluminum-copper-cerium heat-resistant aluminum alloy, comprising:

[0056] S1: a. After mechanically grinding the surface of the metal raw material to remove the surface oxide scale, prepare the materials according to the designed composition ratio; the ingredients are proportioned according to the weight of about 2.5kg per ingot;

[0057] b. Place a high-purity Al ingot in an iron crucible and heat it to 720°C to melt, then keep it warm for 30 minutes; sequentially add the preheated pure Cu, Al-30wt.%Ce, and Al-10wt.%Mn master alloy ingots to the melt, stir and melt, and keep warm for 10 to 20 minutes each time; heat the melt to 760°C, sequentially add the preheated Al-2wt.%Sc and Al-10wt.%Zr master alloy ingots to the melt, stir until all are melted, and keep warm for 10 minutes;

[0058] c. Add refining agent and hexachloroethane in turn to degas and deslag, let it stand and keep warm for 10 to 15 minutes after deslagging, and finally cast it into a mold preheated at 200°C to 300°C to obtain an aluminum alloy ingot; quench the aluminum alloy ingot once it solidifies;

[0059] S2: Solution treatment: keep the alloy ingot at 200℃~300℃ for 12h~24h, then heat it to 350℃~450℃ and keep it for 5h~15h, then heat it to 520℃~537℃ and keep it for 5h~15h, and finally quench it in room temperature water;

[0060] S3: Low temperature aging: The alloy ingot is then kept in an oil bath furnace at 175°C for 18 hours and quenched into room temperature water.

[0061] 3. Performance testing

[0062] The results of mechanical properties test show that the yield strength and tensile strength of the prepared material at room temperature reach 272MPa and 345MPa respectively, the yield strength and tensile strength at 300℃ reach 193MPa and 213MPa respectively, and the yield strength and tensile strength at 400℃ reach 104MPa and 118MP respectively.

[0063] Comparative Example 1

[0064] 1. The aluminum-copper-cerium ternary alloy includes: Cu: 8.2%, Ce: 1.8%, and the rest is Al and inevitable impurities.

[0065] 2. The preparation method of the aluminum-copper-cerium ternary alloy comprises the following steps: using a pit-type resistance furnace

[0066] The specific procedure for preparing the alloy by melting in air is as follows:

[0067] S1: a. After mechanically grinding the surface of the metal raw material to remove the surface oxide scale, prepare the materials according to the designed composition ratio; the ingredients are proportioned according to the weight of about 2.5kg per ingot;

[0068] b. Place a high-purity Al ingot in an iron crucible and heat it to 720°C to melt it, then keep it warm for 30 minutes; add the preheated Al-30wt.% Ce master alloy ingot and pure Cu into the melt in turn, stir and melt them, and keep them warm for 10 minutes;

[0069] c. Add refining agent and hexachloroethane in turn to degas and remove slag. After slagging, let it stand and keep warm for 10 to 15 minutes. Finally, cast it into a mold preheated at 200°C to 300°C to obtain an aluminum alloy ingot; quench the aluminum alloy ingot once it solidifies.

[0070] S2 solution treatment: the alloy ingot is kept at 530℃ for 5h in a resistance furnace and quenched into room temperature water;

[0071] S3 low-temperature aging: The alloy ingot is then kept at 190°C in an oil bath furnace for 15 hours and quenched into room temperature water.

[0072] 3. Organization and performance testing

[0073] The microstructure of the prepared material is Figure 5 As shown in the figure, the heat-resistant aluminum alloy microstructure strengthened by various intermetallic compounds is obtained, that is, the macroscopic microstructure of the material is in the form of dendrites, and micrometer-scale Al is distributed nearly continuously on the grain boundaries. 8 C 4 Intermetallic compound network, θ′ / θ"-Al in the crystal 2 Cu nano-aging precipitation phase.

[0074] Figure 6It is the tensile stress-strain curve of the heat-resistant aluminum alloy material at 300℃ and 400℃ after heat treatment. The mechanical properties test results show that the yield strength and tensile strength of the prepared material at room temperature reached 232MPa and 336MPa respectively, the yield strength and tensile strength at 300℃ reached 155MPa and 166MPa respectively, and the yield strength and tensile strength at 400℃ reached 62MPa and 65MPa respectively. The tensile strength at 300℃ is equivalent to that of ZL206 alloy, 50MPa better than that of ZL207 alloy, and the tensile strength at 400℃ is equivalent to that of ZL207 alloy.

[0075] Compared with Comparative Example 1, since the microstructure of Example 1 is equiaxed crystal, Al is precipitated first. 3 (Sc, Zr) intermetallic compounds exist in the α-Al matrix as nucleating agents, and a high number density of L1 2 Al 3 (Sc, Zr) precipitation phase, and a micrometer-scale intermetallic compound network is nearly continuously distributed at the grain boundaries, so that the yield strength and tensile strength of Example 1 at 300°C reach 200MPa and 210MPa respectively, and the yield strength and tensile strength at 400°C reach 106MPa and 114Mpa respectively.

[0076] Comparative Example 2

[0077] The patent application number is CN202210907398.1, which discloses an aluminum-copper-cerium series heat-resistant aluminum alloy and a preparation method thereof. The heat-resistant aluminum alloy has a micron-scale crystalline phase, with Al 3 The Zr nanoprecipitate phase is a heterogeneous nucleation point precipitated θ′-Al 2 Cu precipitates and promotes RE and Zr elements in θ′-Al 2 The Cu precipitate phase interface is segregated to form a "diffusion barrier layer", which improves the θ′-Al 2 The thermal stability of Cu precipitate phase at 300℃~350℃. After low temperature aging treatment, the alloy needs to be kept at 250~300℃ for 24~50h, which leads to the 2 The Cu precipitate phase dissolves to a certain extent, reducing the θ′-Al 2 The volume fraction and number density of Cu precipitate phase. The yield strength of the alloy at 300°C is 132MPa, the tensile strength is 165MPa, the yield strength at 400°C is 62MPa, and the tensile strength is 71MPa, which still cannot meet industrial needs. Moreover, the heat treatment system for preparing the alloy takes up to about 6 days, which is not allowed for industrial production cycle and energy consumption. 3 The (Sc, Zr) nanoprecipitate phase is a heterogeneous nucleation point precipitated θ′-Al 2Cu precipitate phase precipitate phase, Ce, Mn, Sc and Zr multi-elements are formed in the θ′-Al 2 The Cu precipitate phase interface is segregated to form a multi-layer "diffusion barrier layer", and a high number density and volume fraction of θ′-Al 2 The Cu precipitate phase makes the performance significantly better than that of Comparative Example 2.

[0078] Comparative Example 3

[0079] Patent application number CN202210078369.9 discloses a multi-level intermetallic compound reinforced heat-resistant alloy and its preparation method, Al 89.9 Cu 7.5 Ce 1.5 Mn 0.5 Ni 0.5 Zr 0.1 The heat-resistant aluminum alloy was heat treated by solution treatment at 535℃ / 12h+low temperature aging at 175℃ / 5h+high temperature aging at 300℃ / 100h to obtain a multi-level intermetallic compound microstructure, that is, nano-scale Al2O3 is uniformly precipitated in the grains. 20 Cu 2 Mn 3 and Al 2 Cu intermetallic compound phase, Al in micrometer scale distributed nearly continuously along the grain boundaries 16 Cu 4 Mn 2 Ce、Al 24 Cu 8 Ce 3 Mn、Al 8 C 4 and Al 7 Cu 4 The yield strength and tensile strength of the prepared material at 400°C reached 91MPa and 122MPa respectively, and the tensile strength was slightly better than that of the alloy of the present invention. However, the alloy needs to be heat treated at 300°C for 100h after T6 treatment, which is not allowed for industrial production cycle and energy consumption, while the alloy of the present invention adopts multi-stage solid solution + low temperature aging heat treatment, which only takes 2 days at most.

[0080] Comparative Example 4

[0081] The patent with application number CN202311827346.4 discloses an optimization method for the solid solution process of cerium-containing aluminum alloy and its preparation method. The aluminum-copper-cerium series heat-resistant aluminum alloy undergoes multi-stage solid solution + multi-stage aging heat treatment, which significantly improves the high-temperature mechanical properties of the cerium-containing aluminum alloy. Its yield strength at 300°C can reach 150MPa, and its tensile strength can reach 202MPa. The aluminum-copper-cerium series heat-resistant aluminum alloy of the present invention has a yield strength of 40MPa at 300°C that is better than the comparative example, and a tensile strength that is slightly better than the comparative example by 10MPa. However, the alloy needs to undergo a multi-stage aging heat treatment of ~60h after the multi-stage solid solution treatment, which is not allowed for industrial production cycles and energy consumption. The alloy of the present invention only needs a short aging treatment after multi-stage solid solution to obtain an alloy with better performance than it.

[0082] The tensile strength of the examples and currently common aluminum alloys are summarized in the following table:

[0083] Alloy Type Tensile strength at 300℃ / MPa Tensile strength at 400℃ / MPa state ZL201A 118MPa - T5 ZL206 161MPa - T6 ZL207 115MPa 70MPa T1 Example 1 210MPa 114MPa T6 Example 2 205MPa 112MPa T6 Example 3 213MPa 118MPa T6

[0084] It can be seen from the data in the above table that the tensile strength of the aluminum-copper-cerium heat-resistant aluminum alloy prepared in the present application at 300°C and 400°C is higher than the tensile strength of the currently common aluminum alloys.

[0085] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Even if various changes are made to the present invention, if these changes fall within the scope of the claims of the present invention and their equivalents, they still fall within the protection scope of the present invention.

Claims

1. An aluminum-copper-cerium series heat-resistant aluminum alloy, characterized in that: According to weight percentage, it includes: Cu: 7% to 9.5%, Ce: 1.3% to 2.3%, Mn: 0.1% to 0.5%, Sc: 0.1% to 0.4%, Zr: 0.1% to 0.4%, and the balance is Al and unavoidable impurities; Wherein, the mass relationship between Cu and Ce is Cu=2Ce+4-5; the total molar fraction of the Ce-containing heat-resistant intermetallic compound is ≥2%; The aluminum-copper-cerium series heat-resistant aluminum alloy has a yield strength of 190-200 MPa, a tensile strength of 205-215 MPa and an elongation of 5-8% at 300°C; a yield strength of 100-108 MPa, a tensile strength of 112-120 MPa and an elongation of 10-15% at 400°C.

2. The aluminum-copper-cerium series heat-resistant aluminum alloy according to claim 1, characterized in that: The composition includes, by weight percentage, 8.7% Cu, 1.9% Ce, 0.53% Mn, 0.32% Sc, 0.27% Zr, and the remainder is Al and inevitable impurities.

3. A method for preparing an aluminum-copper-cerium series heat-resistant aluminum alloy, characterized in that: The following steps are involved: S1: calculating the raw material ratio according to weight percentage, smelting the raw materials to obtain an aluminum alloy ingot and quenching the ingot; S2: subjecting the aluminum alloy ingot obtained in step S1 to a solid solution treatment, specifically, maintaining the temperature at 200°C to 300°C for 12h to 24h, then heating the temperature to 350°C to 450°C for 5h to 15h, then heating the temperature to 520°C to 537°C for 5h to 15h, and finally quenching; S3: subjecting the aluminum alloy ingot after the solid solution treatment to low temperature aging, specifically, quenching after keeping the temperature at 160°C to 200°C for 3h to 18h.

4. The method for preparing the aluminum-copper-cerium series heat-resistant aluminum alloy according to claim 3, characterized in that: The step S1 is specifically as follows: placing high-purity Al in an iron crucible, heating it to 720° C. for melting, and then keeping it warm for 30 minutes; sequentially adding preheated pure Cu, Al-30wt.% Ce, and Al-10wt.% Mn master alloy ingots into the melt, stirring and melting them, and keeping them warm for 10 to 20 minutes each time; heating the melt to 760° C., sequentially adding preheated Al-2wt.% Sc and Al-10wt.% Zr master alloy ingots into the melt, stirring until all melted, and keeping them warm for 10 minutes; sequentially adding refining agent and hexachloroethane for degassing and deslagging, standing and keeping warm for 10 to 15 minutes after slagging, and finally casting into a mold preheated at 200° C. to 300° C. to obtain an aluminum alloy ingot; and quenching the aluminum alloy ingot once solidified.

5. The method for preparing the aluminum-copper-cerium series heat-resistant aluminum alloy according to claim 3, characterized in that: The quenching is water quenching.

Citation Information

Patent Citations

  • Aluminum-copper-cerium heat-resistant aluminum alloy and preparation method thereof

    CN115323230A

  • Optimization method and preparation method of solid solution process of cerium-containing aluminum alloy

    CN117626149A

  • Aluminum alloys and related methods and articles

    US20240309494A1

Cited By

  • High-strength heat-resistant Al-Si-Cu-Mg-Fe-V aluminum alloy and preparation method thereof

    CN122484567A